Comparing Treatment Outcomes Among Canadian Military and Civilian Substance Users Attending the Same Residential Treatment Program. Issue 2 (2nd April 2016) - Gavrysh, Iryna; Arbour, Simone; Hambley, Janice; Sivagnanasundaram, Lakshmi
ABSTRACT: Substance use disorder is a concerning health issue, affecting military and civilians alike. Due to exceptional workplace demands and a unique military culture, it is important to explore whether military members respond to addiction treatment in the same manner as their civilian counterparts. The present study compared individual characteristics and addiction treatment outcomes between Canadian military members and civilians attending the same residential program. Results revealed that both groups experienced comparable outcomes at 6 months follow-up. Military members reported significantly higher levels of some aspects of quality of life, compared to civilians. Results support the notion that an integrated, nonmilitary treatment program can be appropriate for military members seeking addiction treatment.